H Factor Deficiency: A Case with an Atypical Presentation - Rocha, AP (2019)
We report a case of an 18-month-old boy with H factor deficiency with atypical presentation: recurrent acute otitis media and several maternal family members with autoimmune disorders (vitiligo, thyroiditis and immune trombocytopenia). Blood tests revealed low C3 and AH50, as well as low properdin and H factor. I factor was normal. CFH gene molecular test confirmed the H factor deficiency diagnosis. This child had none of the typical manifestations of this disorder, namely Neisseria meningitidis infection or renal disease (glomerulonephritis and atypical haemolytic uremic syndrome). Autoimmune family history and correct interpretation of blood tests' results were crucial for this diagnosis.